2017
DOI: 10.1074/jbc.m117.778530
|View full text |Cite
|
Sign up to set email alerts
|

Squamous cell carcinoma–related oncogene (SCCRO) neddylates Cul3 protein to selectively promote midbody localization and activity of Cul3KLHL21 protein complex during abscission

Abstract: Squamous cell carcinoma-related oncogene (SCCRO)/DCUN1D1, a component of the neddylation E3 complex, regulates the activity of the cullin-RING-ligase type of ubiquitination E3s by promoting neddylation of cullin family members. Studies have shown that SCCRO regulates proliferation and Here we show that inactivation of SCCRO results in prolonged mitotic time because of delayed and/or failed abscission. The effects of SCCRO on abscission involve its role in neddylation and localization of Cul3 to the midbody. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 48 publications
(58 reference statements)
1
16
0
Order By: Relevance
“…The most likely cullins to be regulated by neddylation at the cleavage furrow and midbody are CUL1 and 3, both of which have been identified as components of the midbody [38][39][40][41]. The mitotic defects seen in our study after treatment of mitotic cells with MLN4924, including binucleated cells and failed cytokinesis, are also reminiscent of the effects of siRNA knock-down of CUL3 in human cells and in C. elegans [11,38], and siRNA knockdown of the neddylation complex component DCUN1D1/ SCCRO [51]. AURKB, which regulates mitotic progression by phosphorylating a number of substrates involved in mitotic progression including MKLP1 [6], is also a substrate of CUL1 and CUL3 [38,39], and potentially could have altered stability with MLN4924 treatment.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…The most likely cullins to be regulated by neddylation at the cleavage furrow and midbody are CUL1 and 3, both of which have been identified as components of the midbody [38][39][40][41]. The mitotic defects seen in our study after treatment of mitotic cells with MLN4924, including binucleated cells and failed cytokinesis, are also reminiscent of the effects of siRNA knock-down of CUL3 in human cells and in C. elegans [11,38], and siRNA knockdown of the neddylation complex component DCUN1D1/ SCCRO [51]. AURKB, which regulates mitotic progression by phosphorylating a number of substrates involved in mitotic progression including MKLP1 [6], is also a substrate of CUL1 and CUL3 [38,39], and potentially could have altered stability with MLN4924 treatment.…”
Section: Discussionsupporting
confidence: 58%
“…In asynchronous cells, AURKB levels do not appear to be affected by 4-h treatment with 1 μM MLN4924, more than 3 times the dose used in this study [52]. However, a recent study by Huang et al, (2017) [51] indicates AURKB stability in mitosis can be affected by inhibition of neddylation. In this study knock-down of DCUN1D1/SCCRO, which promotes CUL3 activation and localization at the cleavage furrow, stabilized AURKB levels in mitotic cells, delaying the completion of cytokinesis [51].…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Klhl21 is known to bind E3 ubiquitin ligase through Cul3 (Maerki et al, 2009;Courtheoux et al, 2016) and Klhl30 has been identified as a circadian pathway gene involved in the onset of glioma (Madden et al, 2014). Like many other Klhl members, Klhl21 is implicated in diverse types of carcinoma, probably due to its role in cell division (Shi et al, 2016;Huang et al, 2017;Chen et al, 2018). Our findings represent the first expression data for Klhl21/30 subfamily in the chordate nervous system.…”
Section: Discussionmentioning
confidence: 64%
“…Increased expression [147] Aurora B [145,279] KLHL22 Mutation [294] PLK1 [280] KLHL42 Increased expression [148] p60 [149] KLHL18 NA Aurora A [150] KBTBD2 NA p85α [153] IBTKα NA PDCD4 [155] Cheng et al Page 45 Table 6 Summary of evidence for context-dependent neoplastic role of Cullin 3-based E3 ligases. [186,220,295] BRD2/3/4, HDAC6, INF2, DAXX [189,218,239,295] KCTD2 NA Either increased or decreased expression [75,159] c-Myc [75] BTBD34 (TNFAIP1) NA Mutation or overexpression [160,161] RhoA [290] ZBTB16 (PLZF) NA Either increased or decreased expression [162,163] Atgl4L [293] KBTBD7 NA NA TIAM1, Neurofibromin [131,288] KBTBD8 NA NA TCOF1, NOLC1 [289] Table 7 Functional summary of SPOP in mammalian systems.…”
Section: Klhl21mentioning
confidence: 99%